Microphysical analysis for peristaltic flow of SWCNT and MWCNT carbon nanotubes inside a catheterised artery having thrombus: irreversibility effects with entropy. (17th March 2021) - Saleem, Anber; Akhtar, Salman; Nadeem, Sohail; Ghalambaz, Mehdi
The blood flow with carbon nanotubes, examining study case of both single and multi-wall carbon nanotubes is mathematically interpreted. The blood vessel has a sinusoidally fluctuating outer wall and a thrombus is placed at the centre. The restriction to flow is improved by application of a catheter. Entropy is also examined to interpret the irreversibility results. The final results are explained with graphs for exactly obtained mathematical solutions. Streamlines are drawn and they clearly show sinusoidally fluctuating wall on one side and a thrombus on the other side at the centre.